The Second Plan Madras State Review of Progress for 1956-57 and 1957-58 and Programme for 1958-59 Government of Madras - Planning Commission (Planning Commission, 1956)
Agriculture plays a vital role in the economy of our country. It is in mainstay of the bulk of the population. When the First Five-Year Plan was put into operation, the country was faced with serious shortage of food and large quantities of foodgrains had to be imported from foreign countries involving a severe drain on the foreign exchange resources. High priority was given to agricultural schemes in the First Five-Year Plan. The increase of agricultural production achieved during the First Plan made the country largely self-sufficient. In the Second Five-Year Plan, the agricultural programmes have been formulated with a view to producing adequate food to support the increased population and also designed to provide the raw materials for the growing industrial economy.
Government of Madras